No evidence for second leg home advantage in recent seasons of European soccer cups - Amez, S.; Baert, S.; Neyt, B.; Vandemaele, M. (Applied Economics Letters, 2020)
Previous research on the advantage experienced by soccer teams playing the second leg of a knock-out confrontation at home yielded ambiguous evidence. Some studies confirmed the well-established soccer myth that this advantage is substantial while others did not find any significant evidence. We contribute to this literature by analysing all `non-seeded` two-leg confrontations in the UEFA Champions League and the UEFA Europa League between 2010 and 2017. We find that playing the second leg of a knock-out confrontation at home is not associated with a substantially higher chance of proceeding to the next stage of the tournament.